Integrating TPACK and IoT to Enhance Learning Outcomes and Energy Efficiency in Transportation Vocational Education - Dita Rama Insiyanda; Mohammad Obie Restianto; Ataline Muliasari; Yudi Karyanto; Budiharso Hidayat; Guntur Tri Indra Setiawan; Femmy Sofie Schouten; Edi Santosa (Journal of Education Technology, 2025)
Vocational education is expected not only to improve students’ academic achievement but also to contribute tangible solutions to societal challenges, particularly those related to energy efficiency and sustainability in transportation infrastructure. However, the integration of pedagogical innovation with applied technological implementation remains fragmented. This study aims to explore the integration of the Technological Pedagogical Content Knowledge (TPACK) framework with Internet of Things (IoT) technology using Smart WiFi Plugs in transportation vocational education and to evaluate its impact on students’ learning outcomes and public energy efficiency. The study employed a mixed-methods design using a convergent parallel approach. The qualitative component examined instructional innovation through Problem-Based Learning, Project-Based Learning, Service-Learning, and Experiential Learning, while the quantitative component measured electricity consumption before and after IoT implementation in public street lighting, security posts, and student dormitories. Data were analyzed descriptively and complemented by independent-samples t-tests and effect size calculations. The findings indicate improvements in students’ academic performance, reflected in increased mean scores and reduced variability in learning outcomes. In addition, the implementation of IoT-based Smart Plugs resulted in energy efficiency gains ranging from 14.2% to 33.3%, with substantial potential for operational cost savings. This study concludes that integrating TPACK and IoT in transportation vocational education effectively enhances instructional quality while generating meaningful social impact through improved energy efficiency and sustainable infrastructure practices.